Effect of heating temperatures and mould thickness on the geometry shape of in-situ melting magnesium investment casting - Abdul Razak, Siti Nur Faezah (2017)
Magnesium has recently gained more advances used in industrial application, especially in automotive and aerospace component because of its properties that provides light weight structural with high strength and better performance compares with other metal alloy. A new technique of casting magnesium alloys has been explored known as in-situ melting investment casting. Currently, this casting only satisfies to suppress the mould-metal reaction alloys in which air or moisture must be avoided in order to prevent the potential issues such as catastrophic burning and rapid oxidation throughout melting process, but not at the expenses of fluidity within the geometry thin section shell mould. Therefore, the objective of this study is to investigate the effect of temperature and mould thickness on geometry shape of shell mould using the in-situ melting technique. The heating temperature of the granule magnesium alloy involved 650, 700 and 750oC whereas the mould thickness was made in the form of 3 and 5 layers. Based on observation, the result shows that increasing the heating temperature from 650 to 750oC will significantly cause the oxide layer become thicker especially between granules, even though the two condition of flux and argon gas was applied during heating. Meanwhile, decreasing the thickness of the mould could increase melting rate of the granules which causes in small partial fusion between granules at heating temperature of 650 and 700oC with relatively suppressed mould-metal reaction especially at large diameter of geometry ceramic shell mould. This is because before heating process conducted, most of granules already have the oxide gray film. It can be concluded that, the geometric shape of mould gives significant influence to the fluidity of molten metal to flow through the entire shell mould especially the part that having an intricate thin section.